Study of unique aspects of oxidative-nitrosative environment in a radio frequency cold plasma device. (November 2022) - Tiwari, N.; Misra, V.C.; Ghorui, S.
Abstract: The study reports unique aspects of oxidative and nitrosative environment and generation of radicals in a newly developed 13.56 MHz cold atmospheric pressure plasma jet (APPJ) device using optical emission spectroscopy (OES). Signature of generated species, species density, energy, their spatial variation and interaction with liquid medium are investigated. While techniques to achieve controlled generation of atomic oxygen and nitrogen in the same device are identified, distinct ability of pure argon APPJ to break oxygen molecules in air releasing atomic oxygen is an interesting finding. Boltzmann plot technique is used to determine the electron excitation temperature. Time averaged gas temperature is measured using mercury thermometer as well as matching simulated and experimental spectra of A-X band of OH radical. Electron density is determined from spectral broadening of Hα line. Formation of OH radical is detected via its signature A-X band. Measured electron density and electron excitation temperature are of the order of 10 21 per m 3, and 3 eV respectively at the nozzle exit. Standard test strips are used to investigate generation of H2 O2, NO2 and NO3 radicals through interaction of the plasma jet with water as a function of time. Graphical abstract: Image 1